ITPA Deficiency and Ribavirin Level are Still Predictive of Anaemia in HCV–HIV-Coinfected Patients Receiving Ribavirin Combined with a First-Generation DAA (ANRS HC27 Study). Issue 6 (August 2017) - ,; Kheloufi, Farid; Poizot-Martin, Isabelle; Garraffo, Rodolphe; Tavenard, Aude; Quaranta, Sylvie; Renault, Alain; Lavrut, Thibault; Bourlière, Marc; Halfon, Philippe; Piroth, Lionel; Bellissant, Eric; et al.
Background: We aimed to determine the impact of inosine triphosphatase (ITPA) deficiency on ribavirin (RBV)-induced anaemia in HIV–HCV-coinfected patients receiving a triple therapy including the haematotoxic direct-acting antiviral agent boceprevir (BOC). Methods: Patients of the ANRS HC27 BocepreVIH study were genotyped for two ITPA single nucleotide polymorphisms involved in ITPA deficiency. RBV trough concentration (Ctrough ) was determined at week (W)4 and W8. Impact of ITPA deficiency on anaemia, RBV Ctrough, response and haematotoxicity (grade 3/4 anaemia, erythropoietin [EPO] use, RBV dose reduction or transfusion between day [D]0 and W8) was evaluated. Impact of RBV Ctrough on anaemia was also studied. Results: Among the 63 genotyped patients, 33% had a predicted ITPA deficiency. ITPA deficiency was associated with a lower haemoglobin (Hb) decline both at W4 (-1.0 g/dl versus -2.1 g/dl; P =0.02) and W8 (-2.7 g/dl versus -4.1 g/dl; P =0.05). None of the patients with ITPA deficiency received EPO between D0–W8 versus 26% of patients without ITPA deficiency ( P =0.01). RBV Ctrough was associated with Hb decrease both at W4 and W8 and an RBV Ctrough cutoff value of 2 μg/ml was significantly associated with a W4 Hb decline >2 g/dl. Haematotoxicity was significantly associated with a lower W4 Hb level ( P =0.017), absence of ITPA deficiency ( P =0.018) and higher RBV Ctrough ( P =0.012). ITPA deficiency, W4 RBV Ctrough and gender were independent predictors of anaemia at W4. ITPA deficiency was not associated with virological response. Conclusions: ITPA deficiency and RBV Ctrough are still predictive of RBV-induced anaemia in HIV–HCV-coinfected patients treated with RBV combined with a first-generation direct antiviral agent.